Comparing the reliability of older and newer transformer designs - Jagers, Janine Norma (Department of Electrical Engineering, 2015)
This dissertation describes the findings of an investigation that was conducted to determine if the reliability of older designs was significantly different from newer designs, and whether the observed differences (if any) were the result of developments in design, manufacture and technology of transformers during different periods.